Pengawasan Kelaiklautan Kapal Oleh Kesyahbandaran Dan Otoritas Pelabuhan (KSOP) Di Pelabuhan Yos Sudarso Ambon - Sance Ulina Sigiro; Stanislaus K. Ohoiwutun; Pieter S. Soselisa (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
This research was conducted at the Office of the Harbor Master and Port Authority (KSOP) Class I Ambon because of the background of the inaccuracy of the syahbandar in supervision. Informants taken in this study were limited to KSOP employees in the Sailing Safety, Guarding and Patrol Division and Ship Captains. This type of research is descriptive research that describes the SOP of Sailing Approval Letter (SPB) issuance services. The data collection techniques used are observation. Interview and documentation. The data analysis technique used in this research is qualitative descriptive technique. The results of this study indicate that the supervision of the seaworthiness of ships by KSOP has been running quite well, this can be seen from the SOP of issuing letters and ship documents that are on time and checking ships carried out every incoming and outgoing ship. It is recommended that the Ambon Class I Harbor and Port Authority Office (KSOP) further improve its duties and responsibilities in carrying out supervision properly and more thoroughly based on existing and predetermined SOPs, and further emphasize sanctions for errors from both the Syahbandar and the Ship.